The Influence of Android-Based Augmented Reality Learning Media on Student Learning Outcomes in Atomic Model Material - Syamiluddin, Syamiluddin; Ang, Roel; Torres, Alvic; Auditor, Edwin (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to determine the effect of Android-based augmented reality (AR) learning media on student learning outcomes in atomic model material. Methodology: This study is a quantitative study with a quasi-experimental design using a one-shot case study approach. The research sample consisted of 70 grade X students at State Senior High School 29 Jakarta who were given treatment in the form of learning using Android-based augmented reality media. The research instrument was in the form of multiple-choice objective posttest questions that had been validated and equipped with grids. Data analysis was carried out using a simple linear regression test to determine the effect of the use of augmented reality media on student learning outcomes. Main Findings: The results of the analysis show that Android-based augmented reality media has a significant influence on student learning outcomes with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.453. This shows that 45.3% of the variation in student learning outcomes can be explained by the use of augmented reality media. This media helps students understand the abstract concept of the atomic model more visually and interactively. Novelty/Originality of this study: This research is part of a further research (dissemination) that tests the effectiveness of previously developed Android-based augmented reality media. The uniqueness of this research lies in the focus of its implementation on abstract chemical material and the use of experimental design in a real learning environment.